2016
DOI: 10.1002/2016gc006395
|View full text |Cite
|
Sign up to set email alerts
|

Causes of unrest at silicic calderas in the East African Rift: New constraints from InSAR and soil‐gas chemistry at Aluto volcano, Ethiopia

Abstract: Restless silicic calderas present major geological hazards, and yet many also host significant untapped geothermal resources. In East Africa, this poses a major challenge, although the calderas are largely unmonitored their geothermal resources could provide substantial economic benefits to the region. Understanding what causes unrest at these volcanoes is vital for weighing up the opportunities against the potential risks. Here we bring together new field and remote sensing observations to evaluate causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 118 publications
(262 reference statements)
3
100
1
Order By: Relevance
“…Nevertheless, the derived impedance transfer functions were very similar. No systematic differences were observed that could be associated with subsurface changes in the electrical structure in connection with the deformation events detected by both GPS and InSAR (Hutchison, Biggs, et al, ).…”
Section: New Mt Data Along a Cross‐rift Transectmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, the derived impedance transfer functions were very similar. No systematic differences were observed that could be associated with subsurface changes in the electrical structure in connection with the deformation events detected by both GPS and InSAR (Hutchison, Biggs, et al, ).…”
Section: New Mt Data Along a Cross‐rift Transectmentioning
confidence: 97%
“…Pulse‐like surface deformation events on a number of volcanoes located on the central rift axis have been reported through the analysis of satellite imagery (interferometric synthetic aperture radar, InSAR; Biggs et al, ) and give rise to concern about potential geohazards associated with volcanic activity. The silicic peralkaline volcano Aluto has been the target of a number of geological, geochemical, and geophysical studies undertaken in recent years (Fontijn et al, ; Gleeson et al, ; Hutchison et al, ; Hutchison, Biggs, et al, ; Hutchison, Mather, et al, ; Saibi et al, ; Teklemariam et al, ; Wilks, Kendall, et al, ). It is the site for a hydrothermal power plant with three test drillings awaiting integration into the local power grid.…”
Section: The Study Area In the Ethiopian Riftmentioning
confidence: 99%
See 1 more Smart Citation
“…Volcanic activity in the MER has formed both silicic peralkaline “central” volcanoes and distributed mafic cones and lavas (e.g., B. Abebe et al, ; Gibson, ). The poorly known volcanoes of the MER have become the focus of much recent work (Aspinall et al, ; Fontijn et al, ; Hutchison et al, , Hutchison, Fusillo, et al, , Hutchison, Biggs, et al, , Hutchison, Pyle, et al, , Hutchison et al, ; Lloyd, Biggs, Wilks, et al, , Lloyd, Biggs, Birhanu, et al, ; Martin‐Jones et al, ; McNamara et al, ; Rapprich et al, ; Siegburg et al, ; Tadesse et al, ; Vye‐Brown et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The silicic MER volcanoes are in a post‐caldera stage of evolution (Hutchison, Fusillo, et al, ). Four volcanoes have shown recent geodetic unrest (Aluto, Corbetti, Bora and Haledebi), with some deformation associated with ongoing geothermal activity (Biggs et al, ; Hutchison et al, , Hutchison, Biggs, et al, ; Lloyd, Biggs, Wilks, et al, , Lloyd, Biggs, Birhanu, et al, ). Corbetti and Aluto are considered the most active volcanic centers in the rift, with deposits from explosive eruptions implying an eruptive flux of 0.01–0.1 km 3 (magma)/kyr over the past 12 kyr (Fontijn et al, ).…”
Section: Introductionmentioning
confidence: 99%